Understanding the origin of Paris Agreement emission uncertainties - Joeri Rogelj (Nature Portfolio, 2017)
The pledges put forward by each country to meet the goals of the Paris Agreement are ambiguous. Rogeljet al. quantify the uncertainty arising from the interpretation of these pledges and find that by 2030 global emissions can vary by −10% to +20% around their median estimate of 52 GtCO2e yr−1.